The show must go on - virtualisation of sport events during the COVID-19 pandemic - Westmattelmann, D.; Grotenhermen, J.-G.; Sprenger, M.; Schewe, G. (European Journal of Information Systems, 2020)
Due to the high risk of COVID-19 transmission, many sport events, including organised cycling competitions, have been cancelled. Nevertheless, staying active is important for individual well-being and professional athletes need to compete to earn their living. We propose that mixed-reality applications like ZWIFT allow to conduct virtually mediated sports competitions, which resemble traditional sport realistically and could serve as a remedy for this contradiction. To test this proposition, we compare professional cyclists` performance data from virtual competitions with data obtained from traditional cycling races and find that the physical activities are comparable. Thus, we contribute to the discussion on the distinctiveness of sports and eSport. Moreover, we interview 11 professional cyclists, who participated in virtual race series regarding their evaluation of the virtualisation of cycling events. Accordingly, we contribute to the literature on mixed-reality applications by focusing on user perceptions of a novel and physical dimension of virtually mediated interaction. Thereby, we apply the sports digitalisation framework proposed by Xiao et al. (2017). Professional athletes mainly perceive the virtualisation of sport as positive, but also mention some specific risks. Consequently, we derive implications for practice that include the supportive role of virtual sport to help master pandemics such as COVID-19.